2017
DOI: 10.1103/physrevd.95.123509
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Scalar Field Potential in Inflationary Models with a Gauss-Bonnet term

Abstract: We study inflationary models with a Gauss-Bonnet term to reconstruct the scalar field potentials and the Gauss-Bonnet coupling functions from the observable quantities. Using the observationally favored relations for both n s and r, we derive the expressions for both the scalar field potentials and the coupling functions. The implication of the blue-tilted spectrum, n t > 0, of the primordial tensor fluctuations is discussed for the reconstructed configurations of the scalar field potential and the Gauss-Bonne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…We take the following potential and the coupling function for this type, which was first introduced in Ref. [35], as 2…”
Section: Gauss-bonnet Inflation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We take the following potential and the coupling function for this type, which was first introduced in Ref. [35], as 2…”
Section: Gauss-bonnet Inflation Modelsmentioning
confidence: 99%
“…Therefore, in this work, we consider inflationary models with a Gauss-Bonnet (GB) term to estimate the energy spectrum of the PGW and to provide constraints on the reheating parameters. Inflationary models with a GB term are not uncommon, and it is well studied in the context of inflation, dark energy, and the PGW [28][29][30][31][32][33][34][35][36], as well as for reheating [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…While the argument in [9] seems to be general to a large extent, a counterexample is known to exist in the literature: inflation with the nonminimal coupling to the Gauss-Bonnet term [18][19][20][21][22][23][24][25][26][27][28][29]. Though in this case the energy density of the slowly rolling inflaton is dominated by its potential, one can have a positive tensor tilt [18,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…A model with a coupling between the scalar field and the Gauss-Bonnet (GB) G invariant, to study inflationary slow-roll cosmology, was proposed in [29], displaying a phenomenology viable for a wide range of values of the free parameters of the theory, and novel bottom-up reconstruction techniques from the observational indices. Many studies of inflation with this type of coupling have appeared in the literature (for an important stream of related papers see, for example, [30][31][32][33][34][35][36][37][38][39][40]). This same coupling has also been proposed to address the dark energy problem in [41], where it was found that quintessence or a phantom phase may occur in the late time universe.…”
Section: Introductionmentioning
confidence: 99%